Evaluation and diagnostic approach in patient with Perrault Syndrome - Nathania, Rachael Christin; Usman, Steven Yulius; Aryasatiani, Ekarini (Majalah Obstetri & Ginekologi, 2024)
HIGHLIGHTS 1. The rare hereditary condition Perrault Syndrome is characterized by sensorineural hearing loss (SNHL) and ovarian dysfunction2. Cyclic estrogens and progesterone may be given to adolescents with amenorrhea to induce withdrawal bleeding and mimic the menstrual cycle.   ABSTRACT Objectives: A multidisciplinary team, which included a reproductive endocrinologist and an otolaryngologist, identified Perrault Syndrome in a patient with secondary amenorrhea and bilateral sensorineural hearing loss. Case Report: A 16-year-old female presented to the obstetrics and gynecology clinic at a type B hospital with primary amenorrhea for one year. Menarche occurred at age 13, followed by regular menstrual cycles for two years, after which menstruation gradually ceased. She denied dysmenorrhea, constipation, leukorrhea, genital pruritus, growth retardation, and weight loss. The patient expressed concern about potential future infertility. At age 9, she was diagnosed with a viral infection by an ENT specialist due to bilateral hearing loss, leading to emotional disturbances. There was no history of prior medication, family illness, or chronic infections. Born at term via spontaneous vaginal delivery, the patient weighed 3,000 grams. Laboratory tests revealed normal T3 (1.51 ng/dl), FT4 (1.16 ng/dl), prolactin (18.25 ng/ml), estrogen (11 pg/ml), and progesterone (0.1 pg/ml) levels, but elevated FSH (66.46 mIU/ml) and LH (29.97 mIU/ml) levels. Symptomatic treatment included bone conduction hearing aids and estrogen replacement therapy. Conclusion: Perrault Syndrome, a rare hereditary condition, manifests as sensorineural hearing loss (SNHL) and ovarian dysfunction, including primary ovarian insufficiency (POI) and gonadal dysgenesis, in individuals with a 46, XX karyotype. Molecular diagnosis remains challenging. Consultation with a pediatric endocrinologist can guide cyclic estrogen and progesterone therapy to induce withdrawal bleeding in adolescents with amenorrhea. Women at risk of ovarian failure should consider donor eggs or oocyte cryopreservation. Avoiding aminoglycosides and excessive noise is crucial for managing hearing loss.